PEMANFAATAN LIMBAH MASKER SEKALI PAKAI SEBAGAI BAHAN PENGGANTI ASPAL TERHADAP NILAI STABILITAS DAN FLOW - Mutiara Permata Puspita Dewi; Wike Andaresta Elsa Putri; Pricillia Kurniawan; Bella Koes Paulina Cantik (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2023)
During the COVID-19 pandemic, it is essential to adhere to health protocols, one of which includes the use of a disposable mask for personal protection. However, the widespread use of single-use masks has resulted in a new problem, which is the accumulation of mask waste. Therefore, it is necessary to find a solution to reduce the amount of mask waste. One innovative solution to this problem is the utilization of masks in the infrastructure sector. Masks made of polypropylene are advantageous as they act as a good binder. By incorporating an appropriate percentage of mask waste, it is possible to produce bitumen with good parameters. This study aims to evaluate the stability and flow parameters of bitumen mixtures by substituting bitumen with 3-ply disposable mask waste. Experimental testing was conducted by replacing bitumen with mask waste at percentages of 0.5%, 0.75%, 1%, 1.5%, and 2%. The hot mix method was used to mix asphalt with the waste masks at a temperature of 150oC. Sensitivity analysis was performed to determine the impact of the percentage of mask waste on the stability and flow assessment parameters using the Marshall Test. The results of this study indicate that an increase in the percentage of mask waste leads to a sensitive response in the stability and flow values. The optimum percentage of mask waste for the mixture was found to be 1.50%, resulting in stability and flow values of 1020.36 kg and 4 mm, respectively.